Two new species of genus Paratachycines Storozhenko 1990 from China (Orthoptera: Rhaphidophoridae Aemodogryllinae) - Zhang, Feng; Liu, Xian-Wei; Bi, Wen-Xuan (Zootaxa, 2009)
Paratachycines was proposed by Storozhenko in 1990 with the type species, Paratachycines ussuriensis Storozhenko, 1990. Paratachycines includes 15 species belonging to 4 subgenera (Eades et al, 2007): Allotachycines, Hemitachycines, Orphanotettix and Paratachycines. In the present paper, two new species Paratachycines (Paratachycines) hebeiensis sp. nov.; Paratachycines (Hemitachycines) xiai sp. nov. are described. The recently described Paratachycines (Paratachycines) thailandensis Gorochov, 2002 maybe belong to the genus Eutachycines Storozhenko 1990. All specimens are deposited in the Shanghai Entomology Museum, the Chinese Academy of Sciences.